Looking back 16 : Queridas de Rizal - Ocampo, Ambeth R. (Mandaluyong City, Philippines : Anvil Publications, 2021)
Querida, in the Philippines refers to a mistress -- In its original Spanish sense, however, querida/querido means someone beloved or cherished.
1. A Catalogue of women: Rizal's Loves -- 2. The Woman who could have been Mrs. Jose Rizal -- The Other Leonor -- A Letter from Leonor a.k.a "Taimis"-- Rizal's First Love -- Rizal on walang forever -- Osei-san: Rizal in Japan -- Rizal in London: Gettie and Pettie -- Rizal and Prostitution -- Rizal's "Amusements" -- Rizal the Little Bad Boy -- Nelly Bousted, Antonio Luna, and Rizal -- Sour Grapes -- The Lady in the Portrait -- Did Rizal Love Josephine Enough to Retract? -- Unhappy wife of Jose Rizal -- Haggling over the Ultimo Adios -- Rom Over Jose Rizal's Will -- A bracken Forgery -- Josephine Bracken : Woman with a Past -- Josephine Bracken, Widow of Rizal -- 'Mrs. Riza" in the New York Times.
Keywords: RIZAL, JOSE, 1861-1896